Study of the effects of Myrmecodia platytyrea extract on the immune status in Wistar rats / Norwati Jailani - Jailani, Norwati (2012)
Ant plants or Sarang Semut tubers are alternative medicinal plants which have been increasingly used traditionally for a broad range of therapeutic values. The purpose of this study was to investigate the potency of Myrmecodia platytyrea species of ant plants, as immunomodulator by evaluating its effect on lymphocytes subpopulations. In this study, group I was designed as vehicle control while rats in each group II, III and IV, were administered with different dose of extract solution for 14 days. Methanol extract of Myrmecodia platytyrea was made to solution with concentrations of 100, 200 and 400 mg/kg by adding 0.9% normal saline. Lymphocytes subpopulations analysis was carried out by using the flow cytometry analysis. The study demonstrated that Myrmecodia platytyrea tuber increased the percentages of lymphocytes subpopulations as compared to the vehicle control, with the higher immunostimulatory effects have shown by group II (100 mg/kg), followed by group III (200 mg/kg), and the lower effects have exerted by group IV (400 mg/kg). Overall, the results showed that Myrmecodia platytyrea tuber has potential to be developed as immunomodulatory agent.